Estimating switching costs of changing social networking sites - Akihiro Nakamura (International Telecommunications Society (ITS), 2012)
This study's empirical analysis shows that the consumers' switching costs when changing SNS are less than that when changing BB service. SNS switching cost is estimated at JPY 944, while that in BB service is estimated at JPY 2864 (JPY 80 = USD 1 on 21st May 2012). According to these results, the switching cost of the former is approximately one-third of that of the latter. One of the reasons why SNS switching costs are smaller could be because of the current small number of friends on SNS. In this survey, approximately half of the respondents stated that their number of friends on SNS was less than 10.
Keywords: 330; Social Networking Sites (SNS); Switching Costs; Layers; Network Effects; Market Power